The Pattern of Thalassemia in Children at the Department of Child Health, School of Medicine University of North Sumatera/ Dr. Pirngadi Hospital, Medan
A study of the characteristics of childhood thalassemia was conducted at the Sub Department of Pediatric Hematology, Dr. Pirngadi Hospital from June 1979 to May 1989. There were 131 cases, consisting of75 (57.25%) boys and 56 (42.75%) girls with an average of 12 admission every year. The predominant age group was 0-2 years, and the youngest was 3 months old; Javanese ethnic group appeared predominant in 36 (63.15%) cases. Clinical symptoms of anemia were found in 112 (85.49%